Sports Activity After Surgical Treatment of Intra-articular Tibial Plateau Fractures in Skiers. (June 2013) - Loibl, Markus; Bäumlein, Martin; Massen, Felix; Gueorguiev, Boyko; Glaab, Richard; Perren, Thomas; Rillmann, Paavo; Ryf, Christian; Naal, Florian D.
Background: Tibial plateau fractures occur frequently while participating in winter sports, but there is no information on whether skiers can resume sports and recreational activities after internal fixation of these fractures. Hypothesis: Skiers can resume low-impact sports activity after internal fixation of tibial plateau fractures. Study Design: Case series; Level of evidence, 4. Methods: A total of 103 patients were surveyed by postal questionnaires to determine their sports activities at a mean of 7.8 ± 1.8 years after internal fixation of intra-articular tibial plateau fractures. The survey also included the Lysholm score, the Tegner activity scale, and a visual analog scale (VAS) for pain. Results: At the time of the survey, 88% of the patients were engaged in sports activities (rate of return to sports, 88%), and 53% continued to participate in downhill skiing. The median number of different activities declined from 5 (range, 1-17) preoperatively to 4 (range, 0-11) postoperatively ( P < .01). Sports frequency and duration per week did not change: 3 (range, 1-7) preoperatively versus 3 (range, 0-7) postoperatively ( P = .275) and 4 hours (range, 1-16 hours) preoperatively versus 3.5 hours (range, 0-15 hours) postoperatively ( P = .217), respectively. Median values of all outcome scores declined: Lysholm score, 100 (range, 85-100) preoperatively versus 94.5 (range, 37-100) postoperatively ( P < .01); VAS, 0 (range, 0-7) preoperatively versus 1 (range, 0-8) postoperatively ( P < .01). Median Tegner activity scale scores declined in all age groups except for patients aged 51 to 60 years. The ability to participate in sports at the time of follow-up compared with the ability before the accident was rated as "similar" by 57 patients (62.0%) and as "worse" by 35 patients (38.0%). The more severe fracture types, B3 and C3 according to the AO classification system, were associated with poorer outcomes related to return to sports and functional scores. Conclusion: A large percentage of skiers with surgically treated intra-articular tibial plateau fractures cannot continue to participate in downhill skiing; however, the majority could resume an active lifestyle for several years after the trauma. Fracture type seems to be an important factor influencing physical activity and general functional outcome.